La Venus de cobre - Davis, Lindsey; González Trejo, Horacio, 1937-; Davis, Lindsey (Barcelona, España ; Capital Federal, Buenos Aires, Argentina : Edhasa, 2010)
In 70 A.D. in ancient Rome, no one is a saint. Or so thinks Marcus Didius Falco, a private investigator first introduced in the award-winning SILVER PIGS, who's trying to prevent a murder before it happens. When every man a woman marries dies, Falco knows there's smoke and fire--and he'll stop at nothing to untangle the Gordion knot that proves it.
Sequel to: La estatua de bronce.
Sequel: La mano de hierro de Marte.
Online resource; title from PDF title page (Digitalia, viewed July 17, 2015)
Keywords: Falco, Marcus Didius, -- 41- -- Fiction; Private investigators -- Rome -- Fiction; Murder -- Investigation -- Fiction; Husbands -- Crimes against -- Fiction; Rome -- Fiction; Electronic books; Historical fiction